1970
DOI: 10.3126/kumj.v7i3.2728
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of fluorescent microscopy with Ziehl-Neelsen staining and culture for the diagnosis of pulmonary tuberculosis

Abstract: Background: For developing countries with a large number of cases and financial constraints, evaluation of rapid and inexpensive diagnostic methods has great importance. The bacilli in the sputum can be detected microscopically by ZN stain and fluorochrome stain. Objectives : To study the efficacy of fluorescence microscopy in the diagnosis of pulmonary tuberculosis in comparison to Ziehl-Neelsen staining and culture of sputum samples from patients suspected of pulmonary tuberculosis. Materials and methods :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 2 publications
3
21
0
1
Order By: Relevance
“…Lower specificity of LED microscopy compared with conventional ZN microscopy has been reported previously . Most studies found that the specificity of LED microscopy was comparable with that of conventional ZN microscopy. In the present study, the specificity of LED microscopy was slightly lower than that of ZN microscopy, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 69%
“…Lower specificity of LED microscopy compared with conventional ZN microscopy has been reported previously . Most studies found that the specificity of LED microscopy was comparable with that of conventional ZN microscopy. In the present study, the specificity of LED microscopy was slightly lower than that of ZN microscopy, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 69%
“…However, the standard method of sputum examination, that is, ZN staining is not sensitive enough and a large number of these suspected cases miss diagnosis. [5] It is of particular importance in the diagnosis of extrapulmonary disease, in which the acid fast bacilli are present in scanty number or may not be detected at all. Hence, ZN staining alone cannot be relied upon for the diagnosis of tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…6. FM can diagnose more number of Pauci bacillary TB than ZN microscopy (7) so it helps in early diagnosis of TB, reducing the complications of TB such as Post Tubercular Bronchiectasis, fibrosis, haemoptysis, Aspergillosis, BPF, Broncholith, Cavernolith and scar carcinoma. 7.…”
Section: Tuberculosis With Hiv Infectionmentioning
confidence: 99%